Hand-drawn Batik Creation: Combining Batak Karo and Simalungun Ornament - Wahyu Tri Atmojo; Misgiya Misgiya; Sri Wiratma (Budapest International Research and Critics University, 2021)
One of the seven ethnic groups in Northern Island of Sumatra is Batak Karo and Simalungun. They have unique and exquisite ornamental cultural resources. However, these ornaments have not been created in many hand-drawn batik. This study aims to create a hand-drawn batik art work with dabbing techniques using Remasol Batik dyes and dyeing cap techniques using napthol batik dyes. Picture on Batak Karo and Simalungun ornament artifacts were obtained from reference books and direct observation. The forms of Batak Karo and Simalungun ornaments are created through a special method with structured stages starting from design preparation, incubation, execution, confirmation and validation of works. The visual process of creating works of art has resulted in ten works of batik art. Four works in the form of non-functional hand-drawn batik art and six batik artworks that have practical functions. The ten works of batik art show the combination of Karo and Simalungun ornaments. However, not all batik art works are the result of a combination. However, there are written batik art works that only depict Batak Karo ornaments and there are also hand-drawn batik artworks that only depict Simalungun Batak ornaments. The result of the hand-drawn batik creation enefits in developing student entrepreneurship and can add to the repertoire of batik in Indonesia.